2018
DOI: 10.3126/jbm.v5i0.27387
|View full text |Cite
|
Sign up to set email alerts
|

Stock Price Behavior of Nepalese Commercial Banks: Random Walk Hypothesis

Abstract: Using the data set on daily stock prices during the fiscal year 2015/16 (Sept 23, 2015 through Dec 22, 2015), this paper attempts to analyze the random behavior of stock price of Nepalese Commercial Banks by using run test, serial correlation and run tests and martingale random walk hypothesis under heteroscedasticity assumption of standard error. The results conclude that the proposition of Random Walk Hypothesis (RWH) in Nepalese stock markets does not hold true. This conclusion corroborates with the conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…(2015).. Market price of stock is influenced in positively but insignificant by dividend yield & return on assets. The market price of stock has the favorable effect by the EPS, PE ratio and size of the bank (Bam, Thagurathi,, & Shrestha 2018). Silwal, & Napit, (2019) found positive relationship between book value, PE ratio, return on equity of the shares and dividend yield and negative relationship with market size of the company on stock price in Nepalese commercial banks.…”
Section: Literature Reviewmentioning
confidence: 93%
“…(2015).. Market price of stock is influenced in positively but insignificant by dividend yield & return on assets. The market price of stock has the favorable effect by the EPS, PE ratio and size of the bank (Bam, Thagurathi,, & Shrestha 2018). Silwal, & Napit, (2019) found positive relationship between book value, PE ratio, return on equity of the shares and dividend yield and negative relationship with market size of the company on stock price in Nepalese commercial banks.…”
Section: Literature Reviewmentioning
confidence: 93%
“…However, in literature, many studies find that financial time series do not exhibit random walks as assumed by the EMH, and the price variations do not follow the normal distribution. Bam et al (2018) investigated the random walk of the stock prices of the Nepalese Commercial Banks, and found that the stock prices of the Nepalese Commercial Banks are not a random walk process. Rehman et al (2018) examined the random walk of the stock prices of the KSE 100 index, S&P BSE 500 index, and CSE All Share index.…”
Section: Introductionmentioning
confidence: 99%